Exchange Rate Management and Inflation Targeting in the CEE Accession Countries - Fabrizio Iacone; Renzo Orsi (Free University Berlin, Jean Monnet Centre of Excellence, 2002)
We consider a small structural model to describe the transmission mechanism of monetary policy and the dynamics of inflation. We first verify the validity of the general structure estimating it for Germany which represents a sort of benchmark model. At least one of the links required for the transmission mechanism of monetary policy, when we analyse the Central and Eastern European Countries (CEECs), reveals to be not significant when considered on the whole sample. On the contrary the results are closer to a textbook description when the attention is shifted to the second part of the sample only. We interpret this as a piece of evidence indicating that the transition is indeed operating, but it is still ongoing and in some cases it is not complete yet. We also verify that the effects of the exchange rate on both the aggregate demand and on the inflation are in agreement with the economic theory. We conclude that the exchange rate should be actively used to control the inflation in the CEECs.
Keywords: 330; Wechselkurssystem; Geldpolitik; Inflation Targeting; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Monetäre Aussenwirtschaftstheorie; Phillips-Kurve; Osteuropa